منهج فقهاء الشافعية في عرض الفروق الفقهية: Methodology in Presenting of al-Furūq al-Fiqhiyyah by Fukahā in Shafi'i School - Akhmad Hanafi Dain Yunta (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
Several scholars of fiqh of the Shafi'i School in presenting fiqh issues used the method of deciphering aspects of the differences between legal issues that had a similar picture but had differences in terms of the law, which was later known as al-furuq al-fiqhiyyah. Since the beginning of the writing of al-furuq al-fiqhiyyah, there had been some literature that discussed it specifically or which specializes it in a sub-discussion. However, the researcher found in this literature that there are significant differences in the method of presentation among the authors. Because of that, it is considered important to formulate a separate method of approach as a general standard to recognize the character of scientific works on al-furuq al-fiqhiyyah. In this study, the researcher used the inductive istinbat method of approach, by inducing possible and representative works of literature related to al-furuq al-fiqhiyyah in the Shafi'i School. This study found that the Fuqaha of Shafi'i school used four ways in presenting the discussion of al-furuq al-fiqhiyyah, namely: Describing the discussion of al-furuq al-fiqhiyyah in one separate literature, describing it in the literature related to al-farq (differences), and al-istisna' (exception), describing it in the literature that specifically discusses a particular problem or issues, and describes it in the literature that simply inserted a discussion of al-furuq al-fiqhiyyah as a complement.